2022
DOI: 10.3390/ijerph19106226
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Salivary Immunoglobulin A, Stress, and Burnout in a Workplace Mindfulness Intervention: A Pilot Study

Abstract: The purpose of this pilot study was to examine the effectiveness of a 6-week workplace mindfulness- and self-compassion-based intervention (MSCBI) on perceived stress, burnout, immune functioning (assessed with the biomarker Immunoglobulin A), self-compassion, and experiential avoidance compared to a Workplace Stress Management Intervention. Both interventions were contextual, i.e., they were carried out in the workplace setting and during working hours. We followed a randomised controlled trial study design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, the overall perception of stress was significantly improved in both samples, confirming our second hypothesis. In a different study, Martínez-Borrás et al [ 23 ] found a positive effect of mindfulness training in a work environment as well. However, they only investigated a certain aspect of mindfulness (being compassionate) whereas in our study mindfulness was assessed comprehensively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall perception of stress was significantly improved in both samples, confirming our second hypothesis. In a different study, Martínez-Borrás et al [ 23 ] found a positive effect of mindfulness training in a work environment as well. However, they only investigated a certain aspect of mindfulness (being compassionate) whereas in our study mindfulness was assessed comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…It further anticipates burnout [ 18 , 21 ] with less emotional exhaustion and more job satisfaction [ 22 ]. Moreover, it has been suggested that a mindfulness and self-compassion-based intervention (MSCBI) may even be more effective than regular psychoeducational interventions in treating work-related stress and burnout [ 23 ]. Previous studies, however, were often not fully validated due to a lack of control groups.…”
Section: Introductionmentioning
confidence: 99%